2022
DOI: 10.21037/atm-21-6909
|View full text |Cite
|
Sign up to set email alerts
|

SENP1 inhibition suppresses the growth of lung cancer cells through activation of A20-mediated ferroptosis

Abstract: Background: Ferroptosis is a type of cell death driven by iron accumulation and lipid peroxidation, which is involved in the pathogenesis of various tumors. Small ubiquitin-like modifier (SUMO)-specific protease 1 (SENP1) is a critical SUMO-specific protease, which controls multiple cellular signaling processes. However, the roles and mechanisms of SENP1-mediated protein SUMOylation in the regulation of cell death and ferroptosis remain unexplored. Methods:The gene expression of SENP1 and ferroptosis-related g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…However, the associated ferroptosis link between HSP27 and ACSL4 has not been elaborated. Studies have shown that SENP1 can modulate the inflammatory signal A20, which interacts with ACSL4 and SLC7A11 to regulate ferroptosis in lung cancer cells [ 22 ]. Therefore, we suspected that glioma cells transfected with HSP27 lentivirus are associated with a SUMO-related association with ACSL4.…”
Section: Resultsmentioning
confidence: 99%
“…However, the associated ferroptosis link between HSP27 and ACSL4 has not been elaborated. Studies have shown that SENP1 can modulate the inflammatory signal A20, which interacts with ACSL4 and SLC7A11 to regulate ferroptosis in lung cancer cells [ 22 ]. Therefore, we suspected that glioma cells transfected with HSP27 lentivirus are associated with a SUMO-related association with ACSL4.…”
Section: Resultsmentioning
confidence: 99%
“…The study delves into the post-translational regulation of SLC7A11, specifically focusing on SUMOylation as SUMOylation has been shown to be critical for protein functions 21,22…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that SENP1 is associated with tumor drug resistance. For example, Gao et al found that SENP1 was aberrantly overexpressed in lung cancer cells, whose overexpression had a protective effect on alastine or cisplatin-treated lung cancer cells (Gao et al, 2022). In addition, Chen et al found that, SENP1 protein accumulated in large quantities in the constructed human colon cancer cell lines resistant to irinotecan, knockdown of whom reduced the migration ability of cancer cells (Chen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%